Variability in mid‐depth ventilation of the western Atlantic Ocean during the last deglaciation. (9th September 2017) - Voigt, I.; Cruz, A. P. S.; Mulitza, S.; Chiessi, C. M.; Mackensen, A.; Lippold, J.; Antz, B.; Zabel, M.; Zhang, Y.; Barbosa, C. F.; Tisserand, A. A.
Abstract: Negative stable carbon isotopic excursions have been observed throughout most of the mid‐depth ( 1000–3000 m) Atlantic Ocean during Heinrich Stadial 1 (HS1) and the Younger Dryas (YD). Although there is an agreement that these mid‐depth excursions were in some way associated with a slowdown of the Atlantic Meridional Overturning Circulation (AMOC), there is still no consensus on the precise mechanism(s). Here we present benthic stable carbon and oxygen isotopic (δ 13 C and δ 18 O) records from five cores from the western equatorial Atlantic (WEA). Together with published benthic isotopic records from nearby cores, we produced a WEA depth transect ( 800–2500 m). We compare HS1 and YD data from this transect with data from previously published North and South Atlantic cores and demonstrate that the largest negative δ 13 C excursions occurred in the WEA during these times. Moreover, our benthic δ 18 O records require the presence of two water masses flowing from the Southern Ocean, bisected by a Northern Component Water (NCW). Given that δ 18 O is a conservative water mass tracer, we suggest that δ 13 C was decoupled from water mass composition and does not correspond to simple alternations between northern and southern sourced waters. Instead, δ 13 C behaved non‐conservatively during HS1 and the YD. Consistently with our new 231 Pa/ 230 Th record from the WEA transect, that allowed the reconstruction of AMOC strength, we hypothesize that the negative δ 13 C excursions reflect an increase in the residence time of NCW in response to a weakened AMOC, allowing for a marked accumulation of 13 C‐depleted respired carbon at the mid‐depth WEA. Key Points: New benthic foraminiferal δ 13 C records indicate that 13 C‐depleted waters occupied the mid‐depth western equatorial Atlantic during HS1 and YD A greater amount of respired carbon must have been stored in the Atlantic mid‐depth during these intervals Covariation of δ 13 C with 231 Pa/ 230 Th and Mn records suggests a dominant role of ocean circulation over the negative carbon excursions